Teori Maqashid Al-Syari’ah Perspektif Hukum Islam - Rifqi Junaidi, Mohammad; Sohih, Abid (An Nahdhoh Jurnal Kajian Islam Aswaja, 2022)
Talking about maqasid al-shari'ah or the purpose of Islamic law is an important matter in a discussion of Islamic law which does not escape the views of scholars and experts in Islamic law. Some scholars place maqashid syari'ah in the discussion of ushul fiqh, and other scholars explain it as separate material and expand it in the philosophy of Islamic law. If we analyze all the commandments and prohibitions of Allah in the Qur'an, as well as the commands and prohibitions of the Prophet Muhammad in the Sunnah formulated in fiqh, it will be seen that all of them have a specific purpose and nothing is wasted. All of them have a deep wisdom, namely as a mercy for mankind, as emphasized in several verses of the Qur'an, among them in Surah Al-Anbiya': 107, regarding the purpose of the Prophet Muhammad being sent. Mercy for all nature in this verse is interpreted as the benefit of the people. Meanwhile, in simple terms maslahat can be interpreted as something good and can be accepted by common sense. Accepted reason implies that reason can know and understand the motives behind the establishment of a law, namely because it contains benefits for humans, either explained by Allah himself or by means of reason.